Futsal Game Technique Training at Yppk Santo Bernardus Middle School, Timika, Mimika Regency - Trisakti, Jhon Citro; Nurwirhanuddin, Nurwirhanuddin (Abdi Masyarakat, 2025)
The goal of this development research is to produce a book product of a practice model for basic futsal technical skills based on games that can benefit coaches to make it easier for them to implement training materials. This research uses the Research and Development model from Borg and Gall, which consists of ten steps in the research process. The experimental research design is in the form of the two-group pretest posttest design. The subjects in this study were students aged junior high school from YPPK ST. Bernardus Timika, consisting of 40 students with 28 training model items, and 40 students who were not given treatment. The stages in this research include: preliminary research, expert evaluation, product trials consisting of small group try-outs and field try groups, and product effectiveness tests. The effectiveness test of the model uses basic technical skills tests by comparing the control and experimental groups. The experimental group was given This was carried out by giving a pre-test before treatment and a post-test after treatment. Meanwhile, the control group was given a pre-test and post-test but was not given treatment. The comparison test between the control group and the experimental group using SPSS 16 showed passing = 0.030, controlling = 0.002, dribbling = 0.000, shooting = 0.024, or p-value < 0.05, indicating that there were significant differences in the control group and the experimental group before and after the treatment was applied. Therefore, the implementation of a game-based basic technique skills training model for futsal at SMP YPPK ST. Bernardus Timika needs to be conducted to improve students' basic technical skills.